The Influence of Influencer Credibility and Overclaim on Repurchase Intention Through Brand Trust on Scora Products - Anastasia, Aufi; Nurhidayati , Nurhidayati (CV. Publikasi Indonesia, 2025)
The development of digital technology and social media platforms has led to major changes in marketing tactics, especially in the skincare industry. SCORA, as a domestic skincare brand, uses influencer reputation and digital marketing to develop relationships with customers. However, the emergence of overclaim issues in one of SCORA's products has raised doubts about its effect on brand trust and repurchase intention. This study aims to investigate the influence of influencer credibility and overclaim on repurchase intention, with brand trust as a mediating variable. The study employs a quantitative method through a survey questionnaire administered to 100 individuals who have used SCORA products and were affected by the overclaim issue. Data analysis was conducted using multiple linear regression and mediation tests. The expected outcomes of this study are a more comprehensive understanding of the relationship between influencer credibility, overclaim, brand trust, and repurchase intention, as well as practical recommendations for industry players in designing more effective and ethical communication and promotion strategies.